Remote sensing analysis of geological structures in Peninsular Malaysia using PALSAR data - Pour, A. B. (Institute of Electrical and Electronics Engineers Inc., 2016)
Advances in remote sensing technology allow the application of Synthetic Aperture Radar (SAR) data in geological structural analysis for tropical environments. In this investigation, the Phased Array type L-band Synthetic Aperture Radar (PALSAR) satellite remote sensing data were used to analyze major geological structures in Peninsular Malaysia and provide detailed characterization of lineaments and form-lines in the Bentong-Raub Suture Zone (BRSZ) of Peninsular Malaysia, as well as its implication for sediment-hosted/orogenic gold exploration in tropical environments. Major transcrustal lineaments such as the Bentong-Raub Suture Zone (BRSZ) and Lebir Fault Zone, ductile deformation related to crustal shortening, brittle disjunctive structures (faults and fractures) and collisional mountain range (Main Range Granites) were detected at regional scale using PALSAR ScanSAR data. The major geological structure directions of the BRSZ are N-S, NNE-SSW, NE-SW and NW-SE, which derived from directional filtering analysis to PALSAR fine and polarimetric data. The pervasive array of N-S faults in the study area and surrounding terrain is mainly linked to the N-S trending of the Suture Zone. N-S striking lineaments are often cut by younger NE-SW and NW-SE-trending lineaments. Gold mineralized trends lineaments are associated with the intersection of N-S, NE-SW, NNW-SSE and ESE-WNW faults and curvilinear features in shearing and alteration zones. Lineament analysis on PALSAR satellite remote sensing data is a useful tool for detecting the boundary between the Gondwana-derived terranes and major geological features associated with suture zone especially for inaccessible regions in tropical environments.